Development of Modified E-Modules Augmented Reality Android Based to Improve Student’s Interest and Learning Outcomes - Rani, Fadwa; Susilowati, Endang; Yamtinah, Sri (Bioscientist : Jurnal Ilmiah Biologi, 2024)
Scientific and technical advancements have intensified efforts to incorporate technological results into the teaching and learning process. As a result, new advancements in learning systems are required, such as the creation of Augmented Reality-based e-modules. In colloidal material research, Augmented Reality on an Android tablet is employed in modified Chemistry E-modules to increase student engagement and learning outcomes. The objectives of this research are to create e-modules, evaluate their use, and analyze the impact of chemistry e-modules on learning outcomes and student participation. The feasibility of e-modules is determined through the validation test of 9 validators consisting of media experts, linguists and teaching practitioners. While the e-module was tested on 3 scales, namely limited scale, medium scale and wide scale on respondents, namely grade XI students at SMA Islam Terpadu Baitul Muslim, SMA Teladan, SMA TQ Al Mannan in East Lampung Regency. Based on the research, the academic results and attention spans of grade XI pupils are impacted by chemistry e-modules with customized Augmented Reality on colloid material, A 0.005 significance level has been set. Furthermore, the N-gain value indicates a difference in the attention and learning outcomes of grade XI pupils before and after utilizing the program. Students who do not study the material through e-modules have N-gain values in the low category, while students who study the material through e-modules have N-gain in the high category. In the validation test by validators, it is known that the Aiken coefficient value (V-count) is greater than 0.8 with a very good Likert scale interpretation.